Beier Sentence Completion Test Profiles of Adolescents and Emerging Adults With Internalizing and Externalizing Disorders - Koç, Gencay; Çolak, Burçin; Tatlı, Safiye Z.; İlhan, Rifat Serav and Oncu, Bedriye (Adolescent Psychiatry, 2021)
Background: Understanding adolescents' and emerging adults' psychiatric complaints and their relations with psychiatric disorders can be challenging. Beier Sentence Completion Test (BSCT), as a projective test, can be promising in this respect. However, relations between BSCT profiles and adolescent psychopathology are not well known. Aim: This study aimed to examine and compare BSCT profiles of adolescents and emerging adults with internalizing and externalizing disorders. As well as that, the relation of BSCT profiles with depression and anxiety scores was investigated. Objective: To achieve this aim, we retrospectively collected the hospital records of 300 adolescents and emerging adults (aged. 14-21) admitted to an Adolescent Psychiatry Outpatient Unit. Methods: The psychiatric diagnosis of the patients was classified as Internalizing (n = 100) and Externalizing (n = 100) disorder groups; the control group (n = 100) consisted of adolescents and young adults without any psychiatric diagnosis. BSCT, the Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI) were administered on the first admission to all cases before psychiatric evaluation and treatment. BSCT total subfactor (positive, negative, neutral, and non-response) statement scores were compared between groups, and their correlations with BDI and BAI were investigated. Besides, multivariate logistic regression analyses were conducted for estimating any diagnostic group differences, as well as bivariate logistic regression analyses for estimating BDI and BAI cutoff scores with models that included BSCT total subfactor statement scores. Results: It was revealed that lower positive and non-response statements were crucial for distinguishing externalizing and internalizing disorders and that positive and negative statements were correlated with depression and anxiety scores.In the multivariate regression model, these correlations were predictive only for the relationship between internalizing disorders group and low positive statement scores, not higher negative statement scores that can be associated with lack of positive emotional processing in this group. Also, nonresponse statement scores were found to be predictive for externalizing disorder groups. Similarly, BDI cut-off scores were predicted with low positive statement scores. Conclusion: BSCT profiles can be promising for understanding adolescents and emerging adults with internalizing and externalizing disorders. Lack of positive attributions to the self and other domains of life can be important for differentiating adolescent psychopathology.
Keywords: Beier sentence completion test